Recent evidence on modifiable and non-modifiable risk factors for colorectal cancer (CRC): a systematic synopsis of meta-analyses from 2015 to 2017 (Medical Journal of Indonesia, 2019)
Colorectal cancer (CRC) is a common cancer with a huge impact on international public health. This review discusses recent evidence on modifiable and non-modifiable risk factors for CRC using a systematic review method. This systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines on systematic reviews and meta-analyses of observational studies. The literature search was performed on the Ovid MEDLINE database and included publications from 2015 to 2017, followed by a quality assessment and a narrative synthesis. Of the 90 identified articles, there were 13 meta-analyses with statistically significant results. Seven articles discussed modifiable risk factors and six articles discussed non-modifiable risk. The modifiable risk factors with the highest risk were radiotherapy of prostate cancer (pooled odds ratio 1.68; 95% confidence interval [CI] 1.33-2.12). The non-modifiable risk factors with the highest risk was Lynch syndrome (hazard ratio 135.49; 95% CI 111.55-164.57). This review discovered new and previously known risk factors for CRC. Recent evidence shows that research on CRC risk factors is continuing to grow indicating that more studies on risk factors are needed to optimize CRC prevention and early detection.